Synodality: Implications for Seminary and Religious Formation - Vimala Chenginimattam (Asian Horizons, 2025)
A synodal church is the new revolution that is possibly happening in the church in this millennium. Seminary and religious formation have a pivotal role in shaping the future church in a synodal way. Acknowledging the significance of formation in this process, this paper addresses the implications of Synodality in both Seminary and Religious formation. Hence, this paper details different ways as approaches for the integration of formation in a synodal way. It creates a textual space for the discourse of reformations to take place in the formation process. It invites paradigm shifts in the bottom-to-top pedagogy in priestly formation and challenges the integration of spiritual and intellectual formation.